Necrotrophic fungi associated with epidermal microcracking caused by chilling injury in pickling cucumber fruit - Martínez, Juan Antonio; Trujillo, Juan Pablo Fernández (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to visualize the association between microcracking and other epidermal chilling injury symptoms, and to identify rots in cucumber fruit (Cucumis sativus L.) by scanning electron microscopy (SEM). Depressed epidermal areas and surface cracking due to damages of subepidermal cells characterized the onset of pitting in cucumber fruit. The germination of conidia of Alternaria alternata, with some of them evident on the fractures in the cultivar Trópico, occurred after damaging on the epidermis. Before, the chilling injury symptoms became visible, Stemphylium herbarum conidia germinated, and mycelium penetrated through the hypodermis using the microcracks as pathway. In the cultivar Perichán 121 the fungus was identified as Botrytis cinerea.
Keywords: Alternaria alternata; Botrytis cinerea; Cucumis sativus; Stemphylium herbarum; cryoscanning electron microscopy; pitting